Russian Federation : 2019 Article IV Consultation-Press Release; Staff Report. (IMF Staff Country Reports; Country Report, 2019)
In recent years, the authorities have put in place a sound macroeconomic policy framework that has reduced uncertainty and helped weather external shocks. The current macroeconomic policy mix combines moderately tight monetary policy with a broadly neutral fiscal stance. The medium-term growth outlook remains modest due to structural constraints and sanctions. The authorities have implemented some politically difficult measures in the past year (pension reform and a VAT increase) and have announced plans aimed at raising productivity growth, including higher public spending on infrastructure, health, and education. To significantly increase Russia's long-term growth prospects and reduce stagnation risks, deeper efforts are needed to address the large footprint of the state, overbearing regulation, and governance and institutional weaknesses.